From a Medical to a Social Model: The Evolution of Disability Rights in the Peruvian Constitutional Court’s Jurisprudence (2004–2024) - Alfonso Renato Vargas-Murillo; Enlil Iván Herrera-Pérez; Rafael Fortunato Supo Hallasi; Carlos Alberto Cueva Quispe; Ilda Nadia Monica de la Asuncion Pari-Bedoya (Laws)
The evolution of disability rights jurisprudence in Peru’s Constitutional Court (2004–2024) demonstrates a paradigm shift from medical to social models of disability. This research analyzes key Constitutional Court decisions through documentary analysis, identifying three distinct periods: early medical model jurisprudence (2004–2009), transitional incorporation of international standards (2010–2015), and consolidation of the social model (2016–2024). Findings reveal how the Court’s reasoning evolved from focusing on individual impairments and rehabilitation to recognizing disability as arising from societal barriers. The Court progressively developed sophisticated legal standards for disability discrimination, reasonable accommodation, and recognition of communication rights. Despite significant jurisprudential advancement, implementation challenges persist across institutional contexts, evidencing gaps between progressive legal frameworks and practical application. This study contributes to understanding how constitutional courts can drive paradigmatic shifts in human rights protection while highlighting the limitations of judicial interpretation alone in achieving disability rights implementation.